Effective Attentional Focus Strategies after Anterior Cruciate Ligament Reconstruction: A Commentary - Harjiv Singh; Alli Gokeler; Anne Benjaminse (International Journal of Sports Physical Therapy)
Individuals after anterior cruciate ligament reconstruction (ACLR) have a high rate of reinjury upon return to competitive sports. Deficits in motor control may influence reinjury risk and can be addressed during rehabilitation with motor learning strategies. When instructing patients in performing motor tasks after ACLR, an external focus of attention directed to the intended movement effect has been shown to be more effective in reducing reinjury risk than an internal focus of attention on body movements. While this concept is mostly agreed upon, recent literature has made it clear that the interpretation and implementation of an external focus of attention within ACLR rehabilitation needs to be better described. The purpose of this commentary is to provide a clinical framework for the application of attentional focus strategies and guide clinicians towards effectively utilizing an external focus of attention in rehabilitation after ACLR.